PERBAIKAN PERILAKU DAN TEKANAN DARAH PASIEN HIPERTENSI DI RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN SETELAH PEMBERIAN LEAFLET EDUKASI HIPERTENSI DAN TERAPINYA - Yugo Susanto; Riza Alfian (Jurnal Ilmiah Manuntung, 2015)
Hypertension is a condition of systolic blood pressure >140 mmHg and diastolic > 90 mmHg persistenly. Hypertension is as one of major risk factors for cardiovascular disease, kidney failure, and stroke. The prevalence of hypertension in South borneo is 30.8 %. The behavior is a key factor that inhibited blood pressure control that requires intervention to change patient behavior. The aim of this study were to investigate the influence of  pharmacists educational leaflet of hypertension and treatment given to behavior and blood pressure patient of ambulatory hypertension patients at Internal Disease Policlinic Dr. H. Moch Ansari Saleh Banjarmasin hospital. The study was conducted with quasi-experimental design. The ambulatory hypertension patients data were collected prospectively during the period of April until mei 2015. This study involved 45 patients who included in the inclusion and exclusion criteria. Data collection was conducted by to assess the level of the patient’s behavior questionnaires and the blood pressure data were taken from their medical record. The results showed that giving educational leaflet of hypertension and treatment could increased knowledge, attitude, and practice significantly (p<0,05). The average of knowledge and attitude scores in pre measurement 2,60 ± 0,71, 2,44 ± 0,65 increased in post measurement 2,95 ± 0,20, 2,77 ± 0,51 were statistically different p=0,00. The average of practice scores in pre measurement 2,15 ± 0,85 increased in post measurement 2,48 ± 0,75 were statistically different p=0,03. The systolic and diastolic blood pressure also decreased with an average reduction of 14,44 ± 9,18 mmHg for systolic and diastolic was 9,55 ± 10,21 mmHg. Over all it can be conculed that the giving educational leaflet of pharmacist can improve patient behavior. Furthermore, it can decrease the blood pressure (p<0,05).